The connectivity of pore space in mudstones: insights from high‐pressure Wood's metal injection, BIB‐SEM imaging, and mercury intrusion porosimetry. Issue 4 (29th January 2015) - Klaver, J.; Hemes, S.; Houben, M.; Desbois, G.; Radi, Z.; Urai, J. L.
Abstract: Study of the pore space in mudstones by mercury intrusion porosimetry is a common but indirect technique and it is not clear which part of the pore space is actually filled with mercury. We studied samples from the Opalinus Clay, Boom Clay, Haynesville Shale, and Bossier Shale Formations using Wood's metal injection at 316 MPa, followed by novel ion beam polishing and high‐resolution scanning electron microscopy. This method allowed us to analyze at high resolution which parts of a rock are intruded by the liquid alloy at mm to cm scale. Results from the Opalinus Clay and Haynesville Shale show Wood's Metal in cracks, but the majority of the pore space is not filled although mercury intrusion data suggests that this is the case. In the silt‐rich Boom Clay sample, the majority of the pore space was filled Wood's metal, with unfilled islands of smaller pores. Bossier Shale shows heterogeneous impregnation with local filling of pores as small as 10 nm. We infer that mercury intrusion data from these samples is partly due to crack filling and compression of the sample. This compaction is caused by effective stress developed by mercury pressure and capillary resistance; it can close small pore throats, prevent injection of the liquid metal, and indicate an apparent porosity. Our results suggest that many published MIP data on mudstones could contain serious artifacts and reliable metal intrusion porosimetry requires a demonstration that the metal has entered the pores, for example by Wood's metal injection, broad ion beam polishing, and scanning electron microscopy.